HUMAN RIGHTS ISSUES IN INVESTMENT ARBITRATION CASES: A NEW PERSPECTIVE? - Begić Sarkinović, Taida (Pravni zapisi, 2020)
This article addresses recent human rights matters in the context of treaty-based investment arbitration. After having analyzed two recent arbitral awards, Urbaser v. Argentina and Bear Creek v. Peru, the article argues that host states’ counterclaims on the basis of human rights can serve as an effective vehicle for rebalancing investors’ rights and regulatory powers of host states. Both cases illustrate a more progressive approach of investment arbitral tribunals when dealing with human rights issues. Host states’ counterclaims can also provide a door for arbitrating corporate-related human rights violations in the sense that they can ensure the application of international human rights law in investment arbitration cases. International investment promotion for sustainable development requires rebalancing the rights and obligations of states and investors which could help ensure corporate human rights accountability. In this regard, international investment treaties have to be renegotiated in order to include more human rights content targeting investors’ human rights conduct and in that way provide a more balanced approach when disputes arise.
Keywords: treaty-based investment arbitration; human rights law; international investment law; counterclaims; investor obligations